A Conceptual Model on Websites Design Features for Self-Management of Chronic-Diseases Patients - Aini Saludin, Farhana; Maarop, Nurazean; Megat Mohd Zainuddin, Norziha; Mohammad, Roslina; Azmeela Shariff, Sya (International Journal of Engineering and Technology, 2018)
Undeniably, there are several reasons to be connected to the Internet. In healthcare, finding health information from the Internet and websites is common among the global community. Searching health information over the Internet can assists chronic-disease patients in self-managing their health condition. Self-management program with Information Technology empowerment would improve time, distance and traffic barriers because it is easily accessible, up-to-date, and offers tailored feedback to patients` health status. There is great demand of health websites use though at the same time users are facing concerns and limitations due to medical jargons use and navigational problems. Hence, there is a strong reason why more studies need to be conducted in this particular area especially in the design and development of health websites. Based on a review of relevant papers, this paper aims to propose a model for websites design features for self-management of chronic-diseases patients. Ten relevant features of health websites are extracted and proposed in this study. The study may be beneficial to health websites users and eventually improve their health conditions.Â Â